How do Alternative Pressures Affect the Accuracy of the Pressed Juice Percentage (PJP) at Predicting Consumer Juiciness Rating? - M. M. Kline; A. K. Wilfong; K. V. McKillip; J. M. Gonzalez; T. A. Houser; E. A. Boyle; J. A. Unruh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2016)
Texture is the most important sensory trait when evaluating meat products (Gomes et al., 2014). In beef products, tenderness and juiciness interact to form overall texture and mouthfeel. As a result, beef juiciness is one of the most important factors in creating a satisfactory beef eating experience. A recent study by Woolley (2014) developed an instrumental technique for measuring beef juiciness and predicting consumer beef juiciness satisfaction. The method utilizes a texture analyzer to compress cooked beef samples for a period of 8 seconds at 17.6 lb of force and quantifies the percentage of moisture lost as Pressed Juice Percentage (PJP), a predictor of beef juiciness. Results from the initial study found PJP accounts for 20% of the variation in consumer juiciness scores; however, an evaluation of additional pressures is needed to determine if the PJP method can account for an even greater percentage of variation. Thus, the objective of this study was to evaluate the PJP method utilizing three different pressures and determine the relationship of these values to consumer sensory scores for juiciness.
Keywords: pressed juice percentage; pressure; grade